1972
DOI: 10.1136/bmj.3.5818.76
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Recording of Direct Arterial Pressure and Electrocardiogram in Unrestricted Man

Abstract: (Johnson et al., 1969). This is a further demonstration of the biochemical consequences of imbalance between levels of emotional and physical activity. It provides some additional encouragement for those investigating the place of "exercise therapy" in the prevention and treatment of cardiovascular disease.In addition, this study indicates that sudden exposure to intense heat, as in sauna baths, Turkish baths, and presumably the "coffee baths" becoming fashionable in Japan, may contain an element of risk in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1
1

Year Published

1978
1978
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(41 citation statements)
references
References 1 publication
(1 reference statement)
0
39
1
1
Order By: Relevance
“…Blood pressure was measured directly and continuously from the brachial artery on a portable analogue tape recorder as previously described by us. 11 No complications of the intra-arterial technique were encountered in these patients. All patients gave informed consent to these investigations, which were approved by the hospital Ethics Committee.…”
Section: Introductionmentioning
confidence: 73%
“…Blood pressure was measured directly and continuously from the brachial artery on a portable analogue tape recorder as previously described by us. 11 No complications of the intra-arterial technique were encountered in these patients. All patients gave informed consent to these investigations, which were approved by the hospital Ethics Committee.…”
Section: Introductionmentioning
confidence: 73%
“…Lability increases as the blood pressure level rises, though less than when expressed as a percentage of the mean pressure; it also increases with increasing age (9,12). Clinical physiologists have shown that blood pressure becomes more vari-4868 -155-able as the sensitivity of the baroreflexes declines in hypertensive subjects (4,5) and, strangely, the variations in heart rate decline as the blood pressure variability increases (7,13). However, when it is realized that the baroreflex influences the blood pressure in large measure by moderating cardiac function, it can be appreciated that, as the baroreflex sensitivity declines, the heart rate will increase and its variability will decrease.…”
Section: World Hypertension League'mentioning
confidence: 99%
“…Secondary hypertension and cardiac and renal complications were excluded by routine investigations. We used a transducer-perfusion unit initially developed at Oxford (Bevan et al, 1969;Littler et al, 1972) and later perfected and in constant use at Northwick Park Hospital for the past 7 years for measuring ambulatory BP (Millar-Craig et al, 1978b Mean values were plotted on a 24-h axis to obtain circadian curves, and the points making up these curves were then compared before and after treatment. To standardize the activity/inactivity cycle of each patient, the exact time of waking was carefully recorded and these curves normalized around this time so that events about the waking hour could be carefully compared.…”
Section: Methodsmentioning
confidence: 99%